Ensuring the Safety of Students, Faculty and Community During Service-Learning: The Silliman University Experience - Salem, Deborah Mae C. (Silliman Journal, 2022)
Service-Learning at Silliman University began in year 2000 with the approval of a Service-Learning proposal written by Dr. Enrique G. Oracion submitted to the United Board of Christian Higher Education in Asia (UBCHEA) through the International Partnership for ServiceLearning (IPSL) and the formation of Silliman University Center for Extension and Development (SUCED). The initial service-learning had a multidisciplinary approach conducted at Maluay, Zamboanguita. This was participated in by Social Work and Sociology-Anthropology Departments of the College of Arts and Sciences, College of Business Administration, and the College of Nursing (Delfin, 2002). Currently, more academic units of the university have become actively involved in service-learning. Their activities are coordinated by the Institute of Service-Learning with its director Prof. Emervencia L. Ligutom. Having more academic units involved in service-learning means more students and teachers are going out to the community to serve and learn, and more communities in Dumaguete City and in the province of Negros Oriental are getting involved in hosting these students. To add to this growing number of Silliman University students are international students coming in from various universities in Asia and America. The number of international students is growing as more and more universities are partnering with Silliman University in service-learning. The need to ensure the safety of the students and their teachers as well as the communities where they serve and learn is a priority of the units involved in the program. This paper presents some of the best practices of some service-learning units in the university.